Shape of the mitral annulus in normal individuals and dilated cardiomyopathies: computational modeling insights into leaflet stress distribution - Pasta, Salvatore; La Franca, Eluisa; Crascì, Fabrizio; Gentile, Giovanni; Cipriani, Manlio; Faletra, Francesco Fulvio (Frontiers in Physiology, 2025)
Introduction: The mitral valve annulus naturally adopts a saddle shape in systole, likely concentrating systolic stress on the commissures where fibrous trigones are located. This study hypothesized that in patients with dilated cardiomyopathies, where the annulus is large and planar, the stress would be redirected.Methods: Computational modeling was employed to compare the stress distribution in saddle-shaped mitral valves (n.10 patients) with planar annuli seen in dilated cardiomyopathy (n.10 patients) using kinematics of the mitral valve annulus from systole to diastole extrapolated from computed tomography angiography.Results: Simulations revealed high stress near the anterolateral and posteromedial commissures in normal valves, in contrast to high leaflet stress in planar annuli. Significant differences in stress distribution were observed near the anterolateral (S = 0.427 ± 0.053 MPa in normal valves vs S = 0.211 ± 0.123 MPa in diseased valves, p < 0.001) and posterolateral commissures (S = 0.340 ± 0.008 MPa in normal valves vs S = 0.208 ± 0.060 MPa in diseased valves, p < 0.001). Additionally, mitral annulus disjunction was present in healthy patients but absent in those with annulus planarity due to dilated cardiomyopathy.Discussion: This study suggests that while the saddle-shaped annulus focuses leaflet stress on commissures, planar annuli distribute systolic stress over leaflet surfaces. This may trigger embryonic pathways and alter mitral leaflet collagen content, ultimately leading to valve remodeling. Identifying patients with early annular planarity prior to substantial leaflet remodeling may provide early treatments to prevent increasing mitral regurgitation.